2009
DOI: 10.1523/jneurosci.0247-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Short-Latency Visual Input to the Subthalamic Nucleus Is Provided by the Midbrain Superior Colliculus

Abstract: The subthalamic nucleus (STN) is one of the principal input nuclei of the basal ganglia. Using electrophysiological techniques in anesthetized rats, we show that the STN becomes responsive to visual stimuli at short latencies when local disinhibitory injections are made into the midbrain superior colliculus (SC), an important subcortical visual structure. Significantly, only injections into the lateral, but not medial, deep layers of the SC were effective. Corresponding disinhibition of primary visual cortex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 44 publications
5
53
0
Order By: Relevance
“…Fourteen percent of the subthalamic neurons responded in the alpha band firing activity during the early time window (0-500 ms), suggesting their connection with perceptual processing. Neuronal short-latency activity changes related to visual perception have already been found in animal STNs (72)(73)(74), and have been confirmed in humans by distortion of visual evoked potentials due to STN DBS (75). The difference in neural activity between the fixation and picture viewing periods is not necessarily evidence of visual processing, however; it also may reflect other processes, such as an engagement of selective attention, a shift from gaze fixation to scanning eye movements, or other cognitive functions intervening between vision and action, including memory involvement, target selection, Fig.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Fourteen percent of the subthalamic neurons responded in the alpha band firing activity during the early time window (0-500 ms), suggesting their connection with perceptual processing. Neuronal short-latency activity changes related to visual perception have already been found in animal STNs (72)(73)(74), and have been confirmed in humans by distortion of visual evoked potentials due to STN DBS (75). The difference in neural activity between the fixation and picture viewing periods is not necessarily evidence of visual processing, however; it also may reflect other processes, such as an engagement of selective attention, a shift from gaze fixation to scanning eye movements, or other cognitive functions intervening between vision and action, including memory involvement, target selection, Fig.…”
Section: Discussionmentioning
confidence: 88%
“…The STN is anatomically connected to subcortical centers that contain visually responsive neurons (i.e., superior colliculus, pulvinar, amygdala, substantia innominate, and nucleus accumbens) involved in the visual encoding of emotional stimuli (73,77). Given that the visual, attentional, and emotional systems are intensively interconnected, some proportion of the affective neurons also might be expect to respond in the early time window; however, here only one of the neurons was activated during both the early and late time windows.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the basal ganglia may modulate a variable threshold, as proposed by Lo and Wang (2006). Within the basal ganglia loop, an excitatory projection exists from the SC to the subthalamic nucleus (STN) carrying visual information (Coizet et al 2009). Activating the STN increases inhibitory signals from the SNr basal ganglia output structure (Nambu et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The basal ganglia, having no direct access to spinal motoneurons, mediate their influence through relays within the so-called "premotor" neurons located in the thalamus and brainstem, and including the nucleus pedunculopontinus (PPN) and the superior colliculus (SC) [17]. The complex subcortical loops involving the basal ganglia have been studied in detail by Redgrave, McHaffie and others [18][19][20][21][22]. They confirmed that several brainstem structures, such as the PPN, SC, and various pontine and medullary reticular nuclei are closely linked to the basal ganglia through connections involving a relay in the thalamus.…”
Section: The Elaborate "Reptilian" Basal Gangliamentioning
confidence: 99%